Longitudinal changes in knee gait mechanics between 2 and 8 years after anterior cruciate ligament reconstruction. Issue 5 (22nd November 2017) - Erhart‐Hledik, Jennifer C.; Chu, Constance R.; Asay, Jessica L.; Andriacchi, Thomas P.
ABSTRACT: The purpose of this study was to longitudinally investigate changes in knee joint kinematics and kinetics from 2 to 8 years post‐ACLR. Seventeen subjects with primary unilateral transtibial ACLR performed bilateral gait analysis approximately 2 years and 8 years post‐ACLR. Seventeen matched healthy control subjects were also analyzed. Kinematic and kinetic comparisons between the ACLR and contralateral limbs over time were completed using a 2 × 2 (time, limb) repeated‐measures ANOVA. Unpaired Student's t ‐tests were used to compare the ACLR and contralateral kinematics and kinetics to the control group. The ACLR and contralateral limbs had similar gait changes over time. Kinetic changes over time included a reduction in first ( p = 0.048) and second ( p < 0.001) peak extension moments, internal rotation moment ( p < 0.001), adduction moment (first peak: p = 0.002, second peak: p = 0.009, impulse: p = 0.004) and an increase in peak knee flexion moment ( p = 0.002). Kinematic changes over time included increases in peak knee flexion angle in the first half of stance ( p = 0.026), minimum knee flexion angle in the second half of stance ( p < 0.001), and average external rotation angle during stance ( p = 0.007), and a reduction in average anterior femoral displacement during stance ( p = 0.006). Comparison to healthy controls demonstrated improvement in some gait metrics over time. The results demonstrated longitudinal changes from 2 to 8 years after ACLR in knee joint kinetics and kinematics that have been related to clinical outcome after ACLR and the progression of knee OA, and support future larger and comprehensive investigations into long‐term changes in joint mechanics in the ACLR population. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:1478–1486, 2018.